Environmental and Genetic Determinants of Major Chronic Disease in Beijing–Tianjin–Hebei Region: Protocol for a Community-Based Cohort Study - Liu, Kuo; Cao, Han; Guo, Chunyue; Pan, Li; Cui, Ze; Sun, Jixin; Zhao, Wei; Han, Xiaoyan; Zhang, Han; Wang, Zhengfang; Niu, Kaijun; Tang, Naijun; et al. (Frontiers in Public Health, 2021)
Introduction: Personal life style and air pollution are potential risk factors of major non-communicable diseases (NCDs). However, these risk factors are experiencing dramatic changes in Beijing-Tianjin-Hebei (BTH) region in recent years, few cohorts focus on demonstrating risk factors of major non-communicable diseases (NCDs) in this specific region. The current study is a large, prospective, long-term, population-based cohort study which aims at exploring environmental and genetic determinants of NCDs in BTH areas, the results can provide scientific support to the effect on health recommendations for personalized prevention. Methods: A total of 36,380 people aged 18 years or older are obtained by multistage, stratified cluster sampling from 5 cities in baseline assessment. Participants undergo 7 examinations primarily targeting respiratory and circulatory system function, and questionnaires regarding lifestyle behavior, pollutant exposure, medical and family history, medication history and psychological factors. Biochemistry indicators and inflammation markers are tested and biobank is established. Participants will be followed-up every two years. Genetic determinants of non-communicable chronic diseases (NCDs) will be demonstrated by using multi-omics, and risk prediction models will be constructed using machine learning methods based on a multitude of environmental exposure, examination data, biomarkers, psychosocial and behavioral assessments. The significant spatial and temporal differentiation are well suited to demonstrate the health determinants of NCDs in BTH region, which will feed into public health policy with regard to disease prevention and survivorship related aspects.